Communities Influence Social Media in Dealing with ‘Filter Bubbles’ and ‘Echo Chambers’ in The Era of Digital Content Among Students - Hefri Yodiansyah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Searching social media and developing an effective communication perspective are two important aspects of managing a positive online presence and impactful messaging. Here are some tips for achieving both of these things by finding the right social media. Looking for goals, determining goals for using social media. Connect with friends and family, build a professional network, promote business, or participate in discussions on user-specific topics. For social media that have different user demographics, learn the key user characteristics of the target audience's platforms by highlighting the features and functionality offered by each platform. Platforms that have a lot of user interaction and engagement are more likely to build an effective online presence. Looking at various points of view, to avoid the digital era with the terms 'filter bubble' and 'echo chamber', you can actively seek information from various sources and different points of view. Follow social media accounts that represent a variety of views and participate in various discussion groups or forums. For steps users can follow to strengthen privacy, improve the quality of public opinion discussions, and build a more positive and inclusive social media environment.